Hungarian Monitoring, 24 August 1989 . [Magyar rádiófigyelő], 1989. augusztus 24 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
Transcripts of Hungarian national radio programs produced by the Hungarian Monitoring Unit of Radio Free Europe/Radio Liberty. A magyar országos rádióadók műsorainak a Szabad Európa Rádió/Szabadság Rádió Magyar Monitoring Osztálya által készített átiratai. International Politics: - Human chain in the Baltics - If USSR increases military spending, US will not decrease its military spending either - Prague calls foreign press reports of Monday's demonstrations "provocative" - Despite expected complications, Czechoslovak side wishes to put Gabčíkovo-Nagymaros dam to use - Bonn government spokesman briefing on the GDR refugees Domestic Affairs: - Prague police recommend instigating proceedings against Tamás Deutsch and György Herényi, taken into custody on Wenceslaus Square - Volker Rühe's talks with Hungarian Socialist Workers' Party (MSZMP) and opposition politicians - GDR refugees - Journalists will be able to attend discussion of first agenda for three-sided talks - Report on the organized underworld - György Fejti on screening MSMZP property ownership Economy: - Problems of the Ózd industrial region - Chair of an agricultural cooperative on over-regulation of the relationship between agricultural concerns and the state Külpolitika: - A balti élő lánc - Ha a SZU növeli katonai kiadásait, Az Egyesült Államok sem csökkentheti - Prága provokatívnak minősítette a külföldi sajtót, melyek a hétfői tüntetésekről számoltak be - A csehszlovák fél, a várható bonyodalmak ellenére is használatba kívánja venni a bősi vízlépcsőt - Bonni kormányszóvivői tájékoztató az NDK menekültek helyzetéről Belpolitika: - A prágai rendőrség eljárás indítását javasolja a Vencel téren őrizetbe vett Deutsch Tamás és Kerényi György ellen - Volker Rühe megbeszélései MSZMP-s és ellenzéki politikusokkal - NDK menekültkérdés - A háromoldalú tárgyalások első napirendjének tárgyalásakor jelen lehettek az újságírók - Riport a szervezett alvilágról - Fejti György az MSZMP vagyonának átvilágításáról Gazdaság: - Az ózdi iparvidék gondjai - A mezőgazdasági üzemek és az állam kapcsolatának túlszabályozásáról egy tsz-elnök